Role of Criminal Prosecution in the System of Criminal Procedural Institutions - N. V. Lantukh (Теоретическая и прикладная юриспруденция)
The article reveals the concept of the legal institution of criminal prosecution in criminal proceedings, analyzes the definition of the subject and method of legal regulation of criminal prosecution, the subject composition and the object of criminal prosecution. The author considers the rules governing the institution of criminal prosecution, which originates from the general category of a claim in law. The article contains proposals for the development of the theory of criminal prosecution as a criminal procedure institution from the standpoint of identifying its system-forming properties, legal nature, and various degrees of its effectiveness for the criminal process.